THE ROLE OF PARENTS IN SUPPORTING EARLY CHILDHOOD AND PRIMARY SCHOOL EDUCATION IN THE DIGITAL ERA - Abdul Haq AS; Miranu Triantoro; Umy Yonaevy (CV. ADIBA AISHA AMIRA, 2024)
The digital age has brought significant changes in the world of education, especially at the early childhood and primary school levels. This research uses the literature study method to examine this topic. The results reveal that the role of parents is crucial in creating an effective learning environment at home and helping children adapt to digital technology in the context of learning. Some important aspects found include: (1) the importance of parental supervision and guidance in the use of digital devices, (2) the role of parents in selecting and evaluating educational digital content, (3) the balance between digital and non-digital activities is crucial, (4) improving parents' digital literacy, and (5) active cooperation between parents and educational institutions. The research also reveals challenges faced by parents, such as the digital divide between generations and concerns about the adverse effects of technology on children's development.